E-learning course on Mainstreaming Biodiversity for Food and Nutrition (available in English, Portuguese and Turkish) - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
The tool was launched at the Conference of the Parties to the Convention on Biological Diversity. By 15 March 2021, a total of 509 users have registered to take the course (196 male/313 female).; http://www.b4fn.org/e-learning/e-learning/